A comparison of the physicochemical characteristics of the regional cheese Oscypek and the traditional cheese Gazdowski from the Polish Podhale. (10th December 2013) - Kędzierska‐Matysek, Monika; Florek, Mariusz; Skałecki, Piotr; Litwińczuk, Anna; Chruścicki, Adam
<x xml:space="preserve">Abstract</x> The quality of two types of traditional cheese manufactured in Podhale (southernmost region of Poland), that is, Oscypek (regional PDO) and Gazdowski (native traditional product ‐ NTP), was compared. The appearance, sensory qualities, proximate composition and intrinsic traits were evaluated. Oscypek manufactured from mixed (sheep and cow) milk received higher sensory scores for texture, taste and aroma than the traditional Gazdowski cheese made from cow's milk. Furthermore, the Oscypek cheese contained significantly more total solids and protein, but less salt. Composition could be responsible for its more cohesive texture which was defined by significantly greater cohesiveness, greater hardness, springiness, shear force and shear energy.